Symptoms of Anxiety and Depression Are Correlates of Angina Pectoris by Recent History and an Ischemia-Positive Treadmill Test in Patients with Documented Coronary Artery Disease in the Pimi Study - Ketterer, Mark W. (Hindawi Publishing Corporation, 2011)
Objective. We tested the association of specific psychological characteristics in patients having stable coronary disease with the reporting of anginal symptoms during daily activities, and positive exercise testing. Methods. One hundred and ninety-six patients with documented CAD enrolled in the Psychophysiological Investigations of Myocardial Ischemia (PIMI) Study completed an anginal history questionnaire and a battery of psychometric tests. They also underwent standardized exercise treadmill tests. Results. Patients with a recent history of angina were more likely to be female, and had higher Beck Depression (P = .002), State Anxiety (P = .001), Trait Anxiety (P = .03), Harm Avoidance (P = .04) and Muscle Tension (P = .004) scores than patients who had no recent history of angina. Along with several treadmill variables indicating more severe disease state and reduced exercise tolerance, patients who developed angina on a positive treadmill test also displayed higher scores on the Beck Depression Inventory (P = .003) and State Anxiety (P = .004) scales. Conclusions. Several psychological characteristics, and most notably anxiety and depression, are strong correlates of recent angina and angina in the presence of ischemia provoked by treadmill testing.